2015
DOI: 10.1039/c5ra12050k
|View full text |Cite
|
Sign up to set email alerts
|

High-contrast and reversible mechanochromic luminescence of a D–π–A compound with a twisted molecular conformation

Abstract: By integrating a triphenylamino donor (D) and a (2,2-dicyanovinyl)phenyl acceptor (A) with an anthryl π-spacer, a mechanochromic luminescent (ML) D-π-A compound, TPAANDCV, has been constructed. The single crystals of TPAANDCV display efficient green emission with a good fluorescence quantum yield (Ф F ) of 0.35. Upon grinding the crystals, a dramatic emission-colour variation from green to orange-red has been observed, and such a variation can be erased through annealing or solvent-vapour fuming. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…The powder X-ray diffraction (PXRD) measurements (Figure ) revealed that the as-crystallized samples and vapor-fumed or heated solids have identical diffraction patterns, indicating that vapor or heating treatment results in the recovery of the original crystalline phases. On the other hand, the ground solids exhibit a few weak peaks or no diffraction peak, suggesting their amorphous or amorphous-like nature. ,, These observations imply that the well-ordered crystalline states can be destroyed by mechanical force and be restored by thermal or organic vapor stimulus. Additionally, it was found that the DPA-DCNAC-C4 crystal was more sensitive to mechanical stimuli in the grinding process.…”
Section: Results and Disccusionmentioning
confidence: 99%
“…The powder X-ray diffraction (PXRD) measurements (Figure ) revealed that the as-crystallized samples and vapor-fumed or heated solids have identical diffraction patterns, indicating that vapor or heating treatment results in the recovery of the original crystalline phases. On the other hand, the ground solids exhibit a few weak peaks or no diffraction peak, suggesting their amorphous or amorphous-like nature. ,, These observations imply that the well-ordered crystalline states can be destroyed by mechanical force and be restored by thermal or organic vapor stimulus. Additionally, it was found that the DPA-DCNAC-C4 crystal was more sensitive to mechanical stimuli in the grinding process.…”
Section: Results and Disccusionmentioning
confidence: 99%
“…The occurrence of metastable states that, subject to external stimuli, can interconvert or evolve towards the thermodynamically stable state, is a prerequisite for obtaining stimuli‐responsive materials . In this context, mechanochromic dyes, capable of changing their spectral properties when subject to mechanical stress, such as grinding, shearing and pressure, are particularly interesting .…”
Section: Introductionmentioning
confidence: 99%
“…32 The length, and hence the type of p-linker, such as alkene and alkyne bridges, are useful handles to adjust the optical and emissive properties. [33][34][35][36][37][38] These properties can be further tuned by taking advantage of the latent reactivity of alkynes with activated methylenes to extend their functionalization via ''click-chemistry''.…”
Section: Introductionmentioning
confidence: 99%